Tapered microfluidic device for multi-particle separation based on sedimentation principle - Ahmad, Ida Laila (2017)
This thesis presents a label-free tapered microfluidic device for a passive multi-particle separation. Separation process plays a significant role in various industries for example, biomedical diagnostic, food processing and substance purification. The growing needs for continuous separation process lead to the creation of numerous microfluidic based separation devices. Currently, microfluidic based separation devices are associated with limitations in terms of design complexity, sample purity and separation throughput. Therefore, a simple novel passive tapered microfluidic separation device with various taper angles (6°, 12°, 20° and 25°) is proposed for high purity separation of biological and non-biological samples. The device utilizes coupling mechanism between hydrodynamic separations along with sedimentation effect for enhancement of sample purity. Computer-aided design software was employed during design stage while Finite Element Analysis (FEA) software was used for device design’s optimization. The device was fabricated using a soft lithography technique and was characterized in terms of physical dimensions and leakage conditions. Size based separation simulations using FEA were carried out for 3 μm and 10 μm diameters polystyrene (PS) microbeads samples as well as a mixture of 3 μm PS microbeads and Human Cervical Epithelial Carcinoma (HeLa) cells. Through FEA simulations, larger particles were collected at Outlet 1 and small particles were collected at Outlet 2 using 20° and 25° tapered devices. Furthermore, experimental tests were conducted with similar settings and samples as in the simulations. Successful multi-particle separations were observed using 20° and 25° tapered devices at 0.5 to 3.0 μl/min flow rates. These results were in agreement with simulation results obtained. Highest purity of 98% was achieved for both samples with the use of 3.0 μl/min flow rate. As a conclusion, a passive tapered microfluidic device capable of multi-particle separation at high sample purity was developed.